LOGISTICAL PROCESS OF ROAD VEHICLES DISMANTLING AND THEIR ECONOMICAL EFFICIENCY (Perner's Contacts, 2008)
This article deals with problematic of dismantling of end-of-live vehicles. It desribes single steps of dismantling, their procedure and also suggests the possibilities of utilization of scrapping residues.
Keywords: end-of-live vehicle; dismantling; scrapping; utilization